ANALYSIS ON THE FACTORS INFLUENCING THE INCOME OF SMALL MEDIUM ENTERPRISES (CASE STUDY : MITRA BINA SMALL MEDIUM ENTERPRISES UNDER SUPERVISOR OF TELEKOMUNIKASI INDONESIA LIMITED CORPORATION OF EAST JAVA AREA IN SOUTH MALANG) - Sagita, Diana Ari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study analyzed the effect of credit, education and labor to the income Mitra Bina SME Telekomunikasi Indonesia Limited Corporation of East Java Area in South Malang by using multiple linear regression method. Data isÂ obtained from Telekomunikasi Indonesia Limited Corporation of East Java Area in South Malang and the interview with Mitra Bina SME. Testing data used classical assumption test to find out that the data used did not have normality, Heterocedasticity, Autocorrelation, and Multicolleanirity problem. Once the data passes classical assumption test later in the regression using linear regression.The result of this study indicates that through simultaneous and partial variable credit, education and labor significantly influences the income of Mitra Bina SME. Credit variable as capital has the most dominant influence against the income.Keywords: Income, SME, Credit, Education, Labor, classical assumption test, multiple linear regression.